Developing a HOTS-Based History Pocket Book for Academic Competency Test Preparation - Syahri Ramadhan; Melly Tria Utari (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2026)
This study aimed to: (1) to develop a product in the form of a history pocketbook based on HOTS learning, (2) to find the appropriateness percentage value of the history pocketbook based on HOTS learning, obtained through the results of assessment questionnaires from the validators, (3) and to describe the improvement of students' scores of the academic competency test after carrying out learning process using the history pocketbook based on HOTS learning.The process of this study implemented the research and development method proposed by Borg and Gall, which was the process of the research stages being designed and adjusted based on the abilities, needs, and objectives of the research. Meanwhile, data collection techniques were carried out by: (1) observing the participants, (2) interviewing, (3) distributing questionnaires (appropriateness instruments for media experts, material experts, education practitioners, history tutors, and students), and (4) conducting tests (pretest and posttest). The collected data were analyzed using quantitative and qualitative data analysis techniques.The results obtained from this study include: (1) a product in the form of a history pocketbook based on HOTS learning which is portable, practical, and attractive, displays complete information about academic Competency test, and contains complete and updated materials of history subjects, (2) the appropriateness percentage value of the history pocketbook based on HOTS learning, (3) The product achieved high feasibility, with scores of 93.3% from media experts, 87.7% from material experts, 84.6% from history tutors, 87.7% from students in the preliminary trial, and 89.0% from students in the main trial, resulting in an overall average of 88.5%.